Polymer polyol composition for foaming

By reacting with a polymer polyol composition (AC) with low alkalinity and low CO2 content, the problem of low bonding strength of polyurethane foam during spraying is solved, and the foam and substrate are realized Stable adhesion between them and good thermal insulation properties.

CN119431710APending Publication Date: 2025-02-14SHANDONG UNIV OF TECH +1
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202310955418.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When using aqueous alcohol amine compositions as the foaming agent, the polyurethane foam has low bond strength during spraying, easy to peel off from the substrate, and the foam size is unstable, affecting the thermal insulation performance.

Method used

An aqueous alcohol amine composition (AC) is provided, characterized by low alkalinity, low CO2 content and high fluidity, for the preparation of polyurethane rigid foams with polymer polyol compositions. The composition includes ethanol isopropanolamine and ethanol diisopropanolamine, which partially forms a carbonate with CO2 and water, delaying gel time and shortening curing time.

Benefits of technology

The initial adhesion strength and curing strength between the polyurethane foam and the substrate are improved, and the problem of foam falling off during spraying and peeling off after curing is avoided, ensuring the dimensional stability and thermal insulation performance of the foam.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431710A_ABST
    Figure CN119431710A_ABST
Patent Text Reader

Abstract

A foaming composition comprising a novel organic alcohol amine carbonate blowing agent and a polymer polyol, comprising; (I) 100 parts by weight of a polymer polyol comprising: 1) 55-75 wt% of a sucrose starting polyether polyol; 2) 15 to 25 wt% of aromatic polyester polyol; 3) 5 to 15 wt% of a sorbitol starting polyether polyol; 4) 3-7 wt% of toluenediamine starting polyether polyol; (II) 3.5-20 parts by weight of a catalyst, a foam stabilizer and a flame retardant; (III) 6 to 20 parts by weight of ethanol isopropanolamine and ethanol diisopropanolamine carbonate (AC) as a foaming agent. The composition is used for preparing spraying type polyurethane rigid foam.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a foaming polymer polyol composition (white material) comprising a novel organic alcohol amine carbonate foaming agent and a polyether polyol. The composition is used for preparing low-brittle polyurethane rigid foam by reacting with isocyanate, especially for preparing spray-type low-brittle polyurethane rigid foam. Background Art

[0002] Polyurethane rigid foam materials are high-quality thermal insulation materials, widely used in refrigerators, freezers, water heaters, cold chain insulation and other industries. At present, in the field of building exterior wall spraying and pipe winding spraying, people have higher and higher requirements for energy saving and carbon reduction. Therefore, the selection of environmentally friendly foaming agents for the preparation of polyurethane insulation materials in this field is becoming more and more stringent.

[0003] Generally, the polyurethane rigid foam material formed by spraying is prepared by mixing and spraying a polymer polyol composition (white material) with a polyisocyanate (black material), and reacting and curing, wherein the white material contains a polymer polyol of polyether polyol and aromatic polyester polyol (e.g. polyethylene phthalate polyol) and / or toluene diamine polyether polyol as main raw materials, and contains auxiliary agents such as blowing agents, catalysts and foam stabilizers.

[0004] US6326412 B1 discloses ammonium carbamate as a polyurethane foaming agent, wherein the viscosity of the ammonium carbamate is as high as 2200 mPa.s (see lines 51-55 in column 6 of the specification), and the ammonium carbamate is in a viscous or semi-solid state.

[0005] At present, in the case of using a composite foaming agent containing more water, for example, in a foaming agent composed of water and cyclopentane or in a foaming agent composed of water and a hydrofluorocarbon physical foaming agent, if the amount of water used is large, the polyurethane foam formed has a higher open porosity, its size is unstable (prone to shrinkage and deformation), and its thermal insulation performance will decrease.

[0006] In addition, in the spraying process of polyurethane foam, the white material (polymer polyol component A) and the black material (isocyanate component B) are usually mixed by a sprayer (then sprayed on the surface of a substrate (such as a steel plate, a steel pipe, or a concrete structure such as a wall) through a spray gun. Generally, the spraying and foaming is carried out in a spraying manner of 2-3 cm per layer and a total thickness of 20-30 cm. The foam is then formed and cured to obtain a polyurethane rigid foam as a thermal insulation material layer. If a hydrate of a carbonate alcohol amine salt with a higher activity or a higher CO2 content is used as a component of a foaming agent for spraying polyurethane foam, it is found that the foam rises too quickly in the early stage of the foaming reaction, the wet foam expands and rises rapidly, and the surface layer of the foam quickly crusts and solidifies. However, the bonding strength between the substrate and the foam or between two adjacent foam layers will decrease (due to foam shrinkage).

[0007] As a result, the (subsequent) polyurethane coating sprayed on the substrate or sprayed on the cured polyurethane foam coating often cracks or peels off from the substrate or from the cured polyurethane foam layer.

[0008] In addition, in the prior art, aqueous alcohol amines (e.g., carbonates of primary amine alcohol amines (e.g., ethanolamines), and carbonates of some secondary amine diol amines, e.g., carbonate di(diethanolamine) salts, etc.) are used as foaming agents. These alcohol amines have a greater influence on the urethanization reaction between the polymer polyol composition (white material) containing an amine catalyst and polyisocyanates (black material). In particular, some amine foaming agents affect the catalytic action of the amine catalyst, e.g., causing an excessively fast reaction speed in the early stage and insufficient curing reaction in the later stage, affecting the strength of the foam material, and causing the foam material to be dimensionally unstable (high opening rate, easy to shrink and deform). In addition, when aqueous alcohol amines (e.g., triethanolamine hydrate) are used as foaming agents for preparing a spray-coated polyurethane rigid foam with a relatively large thickness, during the spraying process, because the reaction speed is relatively fast and heat is quickly released, a "core burning" phenomenon occurs inside the foam material, which reduces the thermal insulation performance of the foam material, and even causes the foam material to crack from the substrate to form cracks or to crack between two adjacent foam layers to form cracks.

[0009] In addition, US2622099A, US4169856A, US2051486A, GB448373A, GB710861A, GB1387573A, GB642950A, GB760215A, GB655580A and CA1003358A disclose isopropanolamine, ethanolamine or butanolamine prepared by the reaction of aqueous ammonia with propylene oxide or ethylene oxide.

[0010] CN107663157A and CN103435499A disclose a method for producing ethanol diisopropanolamine by reacting ethanolamine with propylene oxide.

[0011] When spray foaming is performed using the CO2- and water-containing olamine composition (AC) and the existing combined polyether (polymer polyol composition) of the prior art, especially when the foam is sprayed onto the surface of cold metal and concrete substrates in cold winter, the problems often encountered are: the initial adhesion strength between the sprayed PU foam layer and the substrate (e.g., steel, such as a steel plate or a steel pipe) or the concrete substrate is low, the wet foam sprayed at a normal spraying speed often peels off and falls off the substrate, and the bonding strength after the foam is cured is low, and peeling occurs between the foam and the substrate after the foam is cured. Summary of the invention

[0012] In order to solve the technical problems existing in the prior art, the inventor of the present application first provides an aqueous alkanolamine composition (AC) (or referred to as an aqueous alkanolamine mixture or an alkanolamine hydrate) for polyurethane foam spraying, which is characterized in that it has lower alkalinity and activity in reaction with isocyanate, lower CO2 content and higher fluidity. Part of the alkanolamine forms carbonate with CO2 and water, that is, the alkanolamine is partially salified. This alkanolamine composition (AC) is used as a foaming agent alone with a foaming agent for polyurethane foam spraying to prepare polyurethane rigid foam. In addition, the foaming agent of the present invention can delay the gel time of polyurethane foam and shorten the curing time. For example, when ordinary alkanolamines (such as diisopropanolamine carbonate or diethanolamine carbonate) are used as foaming agents, the gel time of the sprayed foam is generally 50-60 seconds, but when the CO2-containing and aqueous alkanolamine composition (AC) of the present invention is used, the gel time of the sprayed foam is generally 70-90 seconds.

[0013] Secondly, the inventors of the present application provide a foaming polymer polyol composition for preparing polyurethane rigid foam, i.e., a polyurethane foaming white material. By selecting several special polymer polyols in combination with the CO2-containing and water-containing alcohol amine composition (AC) of the present invention as a foaming agent, the initial adhesion strength (the sprayed wet foam will not fall off the substrate at a normal spraying speed) and the curing strength (no peeling occurs between the foam and the substrate after the foam is cured) between the sprayed PU foam layer and the substrate (e.g., steel, such as a steel plate or a steel pipe) or a concrete substrate are improved. The above-mentioned problems encountered when spraying the foam onto the surface of a metal and concrete substrate at low temperatures in winter are overcome.

[0014] According to the first aspect of the present invention, a foaming polymer polyol composition (white material) comprising a novel organic alcohol amine carbonate blowing agent and a polyether polyol is provided, wherein the composition is used for reacting with an isocyanate to prepare a low-brittle polyurethane rigid foam, especially for preparing a spray-type low-brittle polyurethane rigid foam.

[0015] More specifically, the present invention provides a polymer polyol composition for preparing a low-brittle polyurethane rigid foam (i.e., a polyurethane foaming white material), comprising:

[0016] (I) 100 parts by weight of a polymer polyol, comprising: 1) 55-75 wt% (preferably 57-73 wt%, more preferably 60-70 wt%, for example 62, 64, 65, 66, 68 wt%) of a sucrose-initiated polyether polyol (preferably sucrose-initiated polyoxypropylene polyol), having a hydroxyl value in the range of 290-420 mgKOH / g (preferably 300-400 mgKOH / g, more preferably 305-380 mgKOH / g, for example 310, 320, 330); 2) 15-25 wt% (preferably 17-23 wt%, for example 18, 20, 22 wt%) of an aromatic polyester polyol, having a hydroxyl value in the range of 210-550 mgKOH / g (preferably 220-500 mgKOH / g, more preferably 220-300 mgKOH / g, for example 225, 230, 240 0, 250); 3) 5-15wt% (preferably 7-13wt%, such as 8, 10, 12wt%) of sorbitol-started polyether polyol (preferably sorbitol-started polyoxypropylene polyol), whose hydroxyl value is in the range of 340-520mgKOH / g (preferably 350-490mgKOH / g, such as 360, 370, 380, 400); 4) 3-7wt% (preferably 4-6wt%, such as 5wt%) of toluenediamine-started polyether polyol (preferably toluenediamine-started polyoxypropylene polyol), whose hydroxyl value is in the range of 350-580mgKOH / g (preferably 360-550mgKOH / g, such as 365, 370, 380, 400); wherein the weight percentage is based on the total amount of component 1)-component 4) (i.e., the sum of the percentages of component 1)-component 4) is 100%;

[0017] (II) 3.5-20 parts by weight (preferably 4-18 parts by weight, such as 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 parts by weight) of an auxiliary agent, the auxiliary agent comprising a catalyst, a foam stabilizer and an optional flame retardant; for example, the auxiliary agent comprises 0.5-2.5 parts by weight (such as 1 or 1.5 or 2 parts by weight) of a catalyst, 1-4 parts by weight (such as 1.5, 2, 2.5, 3 or 3.5 parts by weight) of a foam stabilizer and an optional (preferably 0-18 parts by weight, more preferably 0-16 parts by weight, such as 4, 5, 6, 8, 10, 15, 17 parts by weight) flame retardant, based on 100 parts by weight of the polymer polyol;

[0018] (III) 6-20 parts by weight (preferably 7-18 parts by weight, more preferably 8-16 parts by weight, preferably 9-14 parts by weight, such as 10, 11, 12, 15, 17, 19 parts by weight) of a CO2- and water-containing alcoholamine composition (AC) as a blowing agent; the alcoholamine composition (AC) comprises the following components or consists of the following components or consists mainly of the following components:

[0019] (1) ethanol isopropanolamine (A1);

[0020] (2) ethanol diisopropanolamine (A2); and

[0021] (3) Water;

[0022] Wherein, the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.1-9):1, preferably (0.15-8.5):1, preferably (0.2-8):1, preferably (0.3-7.5):1, preferably (0.4-7):1, preferably (0.5-6.5):1, preferably (0.6-6):1, preferably (0.7-5.5):1, preferably (0.8-5):1, preferably (0.9-4.5):1, preferably (1-4):1, preferably (1.2-3.8):1, preferably (1.4-3.6):1, preferably (1.5-3.5):1, preferably (1.7-3.3):1, preferably (1.8-3.2):1, preferably (2-3):1, preferably (2.2-2.8):1;

[0023] More preferably, the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.2-6):1, preferably (0.25-5.5):1, preferably (0.3-5):1, preferably (0.4-4.5):1, preferably (0.5-4):1, preferably (0.6-3.8):1, preferably (0.7-3.7):1, preferably (0.8-3.6):1, preferably (1.0-3.5):1, preferably (1.1-3.3):1, preferably (1.5-3):1, preferably (1.7-2.8):1, preferably (2.0-2.6):1, preferably (2.2-2.4):1;

[0024] wherein the water content is 5-38wt%, preferably 7-35wt%, preferably 8-33wt%, preferably 9-31wt%, preferably 10-30wt%, preferably 12-28wt%, preferably 13-26wt%, preferably 15-25wt%, preferably 16-24wt%, preferably 17-23wt%, based on the total weight of the (final) alcoholamine composition (AC);

[0025] The total content of (A1) + (A2) + water is 90-100 wt %, preferably 92-100 %, preferably 94-100 %, preferably 95-100 %, preferably 96-100 %, preferably 97-100 %, preferably 98-100 %, preferably 99-100 %, such as 99.5 or 99.8 % or 99.9 %, based on the total weight of the (final) alkanolamine composition (AC);

[0026] Wherein, a portion of the alkanolamines in the alkanolamine composition (AC) is neutralized by CO2 so that the CO2 content in the (final) alkanolamine composition (AC) is 1-7wt%, preferably 1.2-6.5wt%, preferably 1.5-6.0wt%, preferably 1.8-5.7wt%, preferably 2-5.5wt%, preferably 2.5-5.0wt%, such as 3, 4 or 4.5wt%, based on the total weight of the (final) alkanolamine composition (AC).

[0027] Preferably, the aromatic polyester polyol is polyethylene phthalate diol, polyethylene phthalate diol and / or polyethylene phthalate / diethylene phthalate diol.

[0028] Preferably, at an ambient temperature of 25°C, the CO2- and water-containing alkanolamine composition (AC) is in the form of a homogeneous liquid having a pressure of 200-1000 centipoise (25°C), preferably 250-900 centipoise (e.g. 300, 400, 500, 600, 700, 800 centipoise).

[0029] Preferably, the alcoholamine composition (AC) is prepared by the following preparation method:

[0030] 1) reacting ethanolamine with propylene oxide in the presence of water to obtain an ethanolamine composition (AC) containing ethanol diisopropanolamine (A2) and ethanol isopropanolamine (A1); wherein the molar ratio of propylene oxide to ethanolamine is (1.2-1.9):1, preferably (1.3-1.85):1, preferably (1.4-1.83):1, preferably (1.5-1.8):1; and the ethanolamine composition can be used in the next step without purification;

[0031] Wherein, the amount of water used in step 1) should be such that the water content in the obtained alkanolamine composition (AC) is as defined above; for example, such that the water content in the alkanolamine composition (AC) is 5-38wt%, preferably 7-35wt%, preferably 8-33wt%, preferably 9-31wt%, preferably 10-30wt%, preferably 12-28wt%, preferably 13-26wt%, preferably 15-25wt%, preferably 16-24wt%, preferably 17-23wt%, based on the total weight of the (final) alkanolamine composition (AC).

[0032] 2) introducing CO2 gas into the obtained alcoholamine composition (AC) to partially neutralize the alcoholamine compound in the composition (AC), thereby obtaining an alcoholamine composition (AC) containing CO2 and water;

[0033] Among them, the amount of CO2 introduced should be such that the CO2 content in the (final) alkanolamine composition (AC) is 1-7wt%, preferably 1.2-6.5wt%, preferably 1.5-6.0wt%, preferably 1.8-5.7wt%, preferably 2-5.5wt%, preferably 2.5-5.0wt%, such as 3, 4 or 4.5wt%, based on the total weight of the (final) alkanolamine composition (AC).

[0034] Preferably, in the resulting alkanolamine composition (AC), the total content of (A1) + (A2) + water is as defined above, i.e. 90-100 wt%, preferably 92-100%, preferably 94-100%, preferably 95-100%, preferably 96-100%, preferably 97-100%, preferably 98-100%, preferably 99-100%, such as 99.5%, 99.8%, 99.9%, based on the total weight of the alkanolamine composition (AC).

[0035] Alternatively, the alcoholamine composition (AC) is prepared by the following preparation method:

[0036] 1) Preparation of ethanol isopropanolamine: react ethanolamine with propylene oxide in the presence of water at a molar ratio of about (0.95-1.05):1 (e.g., about 1:1) to obtain ethanol isopropanolamine (A1); it can be used in the subsequent step 3) without purification;

[0037] 2) Preparation of ethanol diisopropanolamine: react ethanolamine with propylene oxide in the presence of water at a molar ratio of about 1:(1.9-2.1) (e.g., about 1:2) to obtain ethanol diisopropanolamine (A2); it can be used in the subsequent step 3) without purification;

[0038] 3) Preparation of an alcoholamine composition (AC): The product of step 1) and the product of step 2) are mixed to obtain an alcoholamine composition (AC); wherein the amounts of ethanol diisopropanolamine (A2) and ethanol isopropanolamine (A1) are such that the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) in the obtained composition (AC) is as defined above, for example (0.1-9):1, preferably (0.15-8.5):1, preferably (0.2-8):1, preferably (0.3-7.5):1, preferably (0.4-7):1, preferably (0.5-6.5):1, preferably (0.6-6):1, preferably (0.7-5.5):1, preferably (0.8-5):1, preferably (0.9-4.5):1, preferably (1-4):1, preferably (1.2-3.8):1, preferably (1.4-3.6):1, preferably ( 1.5-3.5):1, preferably (1.7-3.3):1, preferably (1.8-3.2):1, preferably (2-3):1, preferably (2.2-2.8):1; more preferably, the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.2-6):1, preferably (0.25-5.5):1, preferably (0.3-5):1, preferably (0.4-4.5):1, preferably (0.5-4):1, preferably (0.6-3.8):1, preferably (0.7-3.7):1, preferably (0.8-3.6):1, preferably (1.0-3.5):1, preferably (1.1-3.3):1, preferably (1.5-3):1, preferably (1.7-2.8):1, preferably (2.0-2.6):1, preferably (2.2-2.4):1; thereby obtaining an alcoholamine composition (AC);

[0039] Wherein, the total amount of water used in step 1) and step 2) should be such that the water content in the (final) obtained alcoholamine composition (AC) is 5-38wt%, preferably 7-35wt%, preferably 8-33wt%, preferably 9-31wt%, preferably 10-30wt%, preferably 12-28wt%, preferably 13-26wt%, preferably 15-25wt%, preferably 16-24wt%, preferably 17-23wt%, based on the total weight of the (final) alcoholamine composition (AC);

[0040] Preferably, in the resulting alkanolamine composition (AC), the total content of (A1) + (A2) + water is as defined above, i.e. 90-100 wt %, preferably 92-100 %, preferably 94-100 %, preferably 95-100 %, preferably 96-100 %, preferably 97-100 %, preferably 98-100 %, preferably 99-100 %, such as 99.5 %, 99.8 %, 99.9 %, based on the total weight of the (final) alkanolamine composition (AC);

[0041] 4) introducing CO2 gas into the obtained alcoholamine composition (AC) to partially neutralize the alcoholamine compound in the composition (AC), thereby obtaining a (final) alcoholamine composition (AC) containing CO2 and water;

[0042] Among them, the amount of CO2 introduced should be such that the CO2 content in the (final) alkanolamine composition (AC) is 1-7wt%, preferably 1.2-6.5wt%, preferably 1.5-6.0wt%, preferably 1.8-5.7wt%, preferably 2-5.5wt%, preferably 2.5-5.0wt%, such as 3, 4 or 4.5wt%, based on the total weight of the (final) alkanolamine composition (AC).

[0043] Preferably, for the above-mentioned olamine composition (AC), the content of CO2 in the olamine composition (AC) is not higher than 7 wt% (more preferably not higher than 6.5 wt%, more preferably not higher than 6 wt%). If the content of CO2 in the olamine composition (AC) is higher than 7 wt%, this may cause the sprayed, cured polyurethane foam layer to often crack from the substrate to form cracks or to crack between two adjacent foam layers to form cracks.

[0044] The inventors of the present application unexpectedly found that the aqueous alcoholamine composition (AC) of the present invention is a low-viscosity liquid at room temperature, which may be because ethanol isopropanolamine and ethanol diisopropanolamine have an asymmetric structure, are not easy to associate and crystallize, and are mixed with each other, resulting in the low viscosity of the alcoholamine composition (AC). Generally, the viscosity or dynamic viscosity (25°C) of the aqueous alcoholamine composition (AC) is 200-900 centipoise (mPa.s), preferably 220-800, more preferably 240-700, more preferably 250-600 centipoise, for example 280, 300, 400, 500, 650, 750 or 850 centipoise. For example, as a single compound, the freezing points (melting points) of diisopropanolamine and triisopropanolamine are 42° C. and 45° C., respectively, and at room temperature, diisopropanolamine and triisopropanolamine are white crystals or solid powders, which indicates that symmetrical diisopropanolamine and triisopropanolamine have a strong tendency to crystallize or associate. Therefore, in order to ensure that the alcoholamine composition (AC) of the present invention has a lower viscosity, it is desirable not to add diisopropanolamine to the alcoholamine composition (AC) as much as possible, and to reduce the amount of triisopropanolamine used.

[0045] Typically, the pH value of the alcoholamine composition (AC) containing alcoholamine partially neutralized by CO2 is in the range of 8-13.5, preferably 8-12, preferably 8.5-11.5, more preferably 9-11, preferably 9.1-10.5, preferably 9.2-10.

[0046] Actually, the aqueous alcoholamine composition (AC) of the present invention comprises alcoholamine carbonate+water+free alcoholamine, and therefore, it is a composite foaming agent with low viscosity.

[0047] In the present application, "optional" means with or without (0).

[0048] In addition, the inventors of the present application unexpectedly discovered that the above-mentioned aqueous alcohol amine composition (AC) of the present invention has good miscibility (or compatibility) in the dry white material formed by (I) polymer polyol and (II), and after being mixed, they can form a transparent, homogeneous and low-viscosity white material (i.e., a foaming polymer polyol composition for preparing polyurethane rigid foam).

[0049] The above-mentioned alcohol amine composition (AC) of the present invention is directly used as a foaming agent for preparing polyurethane rigid foam, and is particularly suitable for use in the spraying of polyurethane foam.

[0050] The present invention also relates to the use of the above-mentioned alcoholamine composition (AC) as a blowing agent for preparing (spray-type) rigid polyurethane foam materials, especially as a blowing agent for spraying rigid polyurethane foam.

[0051] In addition, the above-mentioned olamine composition (AC) of the present invention can also be used in combination with a small amount of a hydrofluorocarbon physical blowing agent (F2) having a boiling point in the range of 15-41° C. Preferably, the physical blowing agent (F1) is one or more (e.g., a combination of two, three, four or five) selected from HCFC-141b, HFC-245fa, HFC-365mfc, LBA and hexafluorobutene.

[0052] The thermal conductivity λ (w / m·k, 20°C) of the spray polyurethane rigid foam of the present invention is generally lower than 0.02250, preferably lower than 0.02240, more preferably lower than 0.02235, more preferably lower than 0.02230, more preferably lower than 0.02220, more preferably lower than 0.02210.

[0053] The compressive strength of the spray polyurethane rigid foam of the present invention (in the direction perpendicular to the substrate, for example, when the density of the foam is about 35 Kg / cm 3 ) is 240-285 (KPa), preferably 245-270 (KPa), preferably 250-267 (KPa), preferably 255-265 (KPa).

[0054] Advantages of the present invention

[0055] 1. In the olamine composition (AC) of the present invention, only a part of the olamine is neutralized by CO2. In addition, by selecting the special polymer polyols 1)-4), the following phenomenon often encountered when using the olamine composition with a higher CO2 content in the prior art as a foaming agent and other polyether polyol compositions with higher reactivity can be avoided during the foam spraying process: if a polyether polyol composition with higher reactivity is used in a larger amount and a foaming agent composition (or olamine composition) with a higher CO2 content is used, then in the spraying operation, in the early stage of the foaming reaction (the reaction system has not yet fully gelled), the reaction is too rapid, and the foaming agent composition (or olamine composition) with a higher CO2 content is heated and rapidly releases a large amount of CO2 gas, causing the wet foam sprayed onto the substrate (stainless steel or concrete) or onto the cured foam layer to expand rapidly and fall from the substrate. In addition, the cured foam has a high brittleness, so it shrinks and deforms slightly, resulting in cracks between the cured foam material and the substrate or between two adjacent cured foam layers. Especially when spraying in cold winter, these problems are particularly prominent. The present invention can overcome the foam cracking problem by selecting a specific polymer polyol when using a special foaming agent alcohol amine composition (AC): there are almost no small molecular compounds in the sucrose-started polyether polyol (preferably sucrose-started polyoxypropylene polyol) and it has a suitable hydroxyl value, so the prepared foam has low brittleness. The sorbitol-started polyether polyol (preferably sorbitol-started polyoxypropylene polyol) has good compatibility with the chemical foaming agent (AC) and has a suitable hydroxyl value, which is conducive to the formation of fine pores. Compared with the ethylenediamine-started polyether polyol, the toluene diamine-started polyether polyol (preferably toluene diamine-started polyoxypropylene polyol) has lower activity and a suitable hydroxyl value (lower viscosity). Since the chemical foaming agent AC has the effect of improving the reaction activity, the use of the toluene diamine-started polyether polyol and the use of a polyester polyol with lower viscosity and lower activity can effectively reduce the reaction activity of the overall material and improve the dimensional stability and bonding strength of the foam.

[0056] 2. The alcoholamine and water in the alcoholamine composition AC of the present invention are conducive to promoting the later crosslinking reaction of the entire foaming reaction (forming a crosslinking network in the cell wall), and the obtained foam has ideal strength and high dimensional stability.

[0057] 3. On the one hand, due to the structural asymmetry of the olamine molecules and the mutual doping between different olamines, the olamine composition (AC) of the present invention has a lower viscosity, so that the prepared white material has good fluidity, and therefore, it is suitable as a blowing agent for the spraying of polyurethane rigid foam. On the other hand, they have good compatibility or miscibility with the dry white material for foaming, so they can be easily and quickly mixed with the dry white material for foaming (to achieve miscibility at the molecular level) to form a uniform, transparent (homogeneous) and well-fluid foaming system (white material), and in the foaming reaction they have a nucleation effect (foaming point) to promote uniform foaming, and therefore, a spray polyurethane rigid foam with good pore microstructure, closed porosity and strength properties can be obtained.

[0058] 4. In the early stage of the foaming process using the foaming agent composition, the carbonate alcohol amine salt hydrate produces a good nucleation effect, that is, the prototype of the foam cells is produced, and the physical foaming agent is heated and gasified in the middle and late stages of the foaming process to further expand the foam cells. The early nucleation effect makes the final PU foam have a very excellent microstructure: the size of the foam cells is smaller, the size of the foam cells is more uniform, the number of foam cells per unit volume is more (from the SEM photo, the number of foam cells per unit area is more), the alcohol amine and water make the foam cell wall more fully cross-linked (the foam has a higher strength at a lower foam density), the foam cell wall is thinner, the foam has a higher air tightness (attributed to the fully cross-linked network on the foam cell wall), and the closed cell rate is higher. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 is a SEM photograph of the foam of Example 1.

[0060] Figure 2 This is a SEM photograph of the foam of Example 2.

[0061] Figure 3 is a photograph of a cross section of the foam of Comparative Example 1.

[0062] Reference numerals: 1: crack between foam and substrate (cement board); 2: crack between two adjacent foam layers; 3:

[0063] Substrate (cement board).

[0064] Figure 4 The product of Preparation Example 4 1 H-NMR spectrum.

[0065] Figure 5 The product of Preparation Example 1 1 H-NMR spectrum. DETAILED DESCRIPTION

[0066] The present invention further describes the technical scheme in detail through the following examples, but the present invention is not limited to these examples.

[0067] Unless otherwise specified, the devices used in the examples are all devices commonly used in the art and commercially available on the market.

[0068] Method for measuring the content of alcoholamines: In the embodiments, the method for measuring the content of various alcoholamines (such as ethanol isopropanolamine, ethanol diisopropanolamine or triisopropanolamine) in the aqueous alcoholamine mixture (AC) (or aqueous alcoholamine composition or alcoholamine hydrate) can be carried out by gas chromatography, wherein the gas chromatograph is equipped with a hydrogen flame ionization detector (FID), and the mass concentration of the alcoholamine compound is about 10 mg / mL, which is a standard solution. Gas chromatography conditions: HP-5 capillary column (30m×0.32mm id×0.25μm, 5% phenyl methyl-siloxane); the column temperature was programmed, the initial temperature was 80℃, maintained for 3min, then increased to 250℃ at a rate of 25℃ / min, and maintained for 5min; the injection port temperature was 250℃; the detector temperature was 260℃; the carrier gas was high-purity nitrogen with a flow rate of 1.5mL / min; the fuel gas was hydrogen with a flow rate of 30mL / min; the auxiliary gas was air with a flow rate of 300mL / min; the tail gas was nitrogen with a flow rate of 25mL / min; the injection method was split injection, with a split ratio of 30:1; the injection volume was 1μL.

[0069] In the present application, the commonly used polyether polyols (polyoxypropylene polyols) and (aromatic) polyester polyols for preparing polyurethane foams or for use in foaming compositions are selected from the following varieties: polyether polyols (polyoxypropylene polyols), for example, polyether polyol 8310 (sucrose initiator polyoxypropylene polyol, hydroxyl value 310) and polyether polyol 4110 (sucrose initiator polyoxypropylene polyol) of BEFAR GROUP CO., LTD., polyether polyol 8038 (sorbitol initiator polyoxypropylene polyol, hydroxyl value 380) of Jiahua Chemical Co., Ltd., polyether 450 (sorbitol initiator polyoxypropylene polyol, hydroxyl value 450) of Nanjing Hongbaoli Co., Ltd., MN500 (glycerol initiator polyoxypropylene polyol) and SA460 of Shandong Bluestar Dongda Chemical Co., Ltd. (sorbitol initiator polyoxypropylene polyol), SA460 (sorbitol initiator polyoxypropylene polyol), SU380 (sucrose initiator polyoxypropylene polyol) and SA380 (sorbitol initiator polyoxypropylene polyol) of Zibo Noli Chemical Co., Ltd., YD8260 (polyoxypropylene polyol with sucrose and diethylene glycol as initiators), YD401P (toluenediamine type polyoxypropylene polyol, hydroxyl value 400±15mgKOH / g, viscosity 13000±2000 (mPa.s 25°C)), YD401 (toluenediamine type polyoxypropylene polyol, hydroxyl value 400±15mgKOH / g, viscosity 15000±2000 (mPa.s 25°C)), YD403 (ethylenediamine initiator polyoxypropylene polyol, hydroxyl value 770±40mg KOH / g), YD460 (toluenediamine type polyoxypropylene polyol) and YD-4110 (polyether polyol, hydroxyl value 460mg KOH / g), and SD7100 (toluenediamine type polyoxypropylene polyol) of Shanghai Dongda Chemical Co., Ltd.; and (aromatic) polyester polyols, for example, XCPA220-1 (aromatic polyester polyol, hydroxyl value 220mg KOH / g) of Asahikawa Chemical (Suzhou) Co., Ltd. KOH / g), polyester polyol PS4051, PS4027 or PS3152 from Nanjing Jinling Stepan Chemical Co., Ltd., polyester polyol CF6320 (hydroxyl value 320 mgKOH / g), CF6245, CF6200, CF6300 and CF6255 from Jiangsu Fusheng New Materials Co., Ltd., and polyester polyol DM2003 from Beijing Oriental Meilong Chemical Technology Co., Ltd.

[0070] Commonly used catalysts are selected from: 33LV (A-33): 33% triethylenediamine in dipropylene glycol solution, N,N-dimethylethanolamine, N,N-dimethylbenzylamine, 70% bis(dimethylaminoethyl) ether in dipropylene glycol solution, 70% potassium octoate in diethylene glycol solution, dibutyltin dilaurate, PT303, PT304, potassium acetate, PC-8 (N,N-dimethylcyclohexylamine), PC-5 (N,N,N,N,N-pentamethyldiethylenetriamine), PC-41 (tris(dimethylaminopropyl)hexahydrotriazine), triethanolamine, JXP-508, JXP-509, TMR-2 (2-hydroxy-N,N,N-trimethyl-1-propylamine formate, Air Products and Chemicals, USA), TMR-3, TMR-4, Dabco 2040 (Evonik Chemicals). Commonly used silicone oil foam stabilizers or silane surfactants: B8525 and B8408 of Evonik Degussa (China) Investment Co., Ltd., AK-158, AK-8805, AK-8812, AK-8809, AK-8818 and AK-8860 of Jiangsu Meside Chemical Co., Ltd., DC8545, DC1990, DC5188, DC6070, DC3042 and DC3201 of Gas & Chemicals, and silicone oil 8841 of Shanghai Maihao Chemical Technology Co., Ltd. Non-silane surfactants: LK-221 and LK-443 of Gas & Chemicals. Commonly used flame retardants: flame retardant TCPP (Jiangsu Yak Chemical Co., Ltd.), TCPP (Qingdao Lianmei Chemical Co., Ltd.), TCEP, DMMP, ammonium chloride, aluminum hydroxide powder, DM1201, DM1301, tetrabromophthalic anhydride diol.

[0071] The following describes a method for preparing an amine carbonate chemical foaming agent (i.e., an amine carbonate hydrate) by CO2 aeration.

[0072] The water content of the carbonate ethanolamine salt hydrate measured by the Karl Fischer method = the amount of free water in the hydrate + the amount of water produced by the decomposition of the carbonate and optionally the bicarbonate. Therefore, the content of free water (wt%) in the carbonate ethanolamine salt chemical blowing agent (F1) (i.e., carbonate ethanolamine salt hydrate) = (the water content of the carbonate ethanolamine salt hydrate measured by the Karl Fischer method) - (the amount of water produced by the decomposition of the carbonate and optionally the bicarbonate). For example, the water content in the alcoholamine composition (AC) described in the present application refers to the water content measured by the Karl Fischer method.

[0073] The test methods for various parameters of polyurethane rigid foam are carried out with reference to the following Chinese national standards GB:

[0074]

[0075] In the above table, the Z direction represents the vertical direction of the foam sample (i.e., the direction perpendicular to the substrate), and the X direction and the Y direction represent two mutually perpendicular directions on the same horizontal plane of the sample.

[0076] Viscosity refers to the dynamic viscosity "centipoise (cP)" at 25°C.

[0077] Preparation Example 1 (preferred)

[0078] 24.42 kg of ethanolamine (molecular weight 61, 400.3 mol) and 12.24 kg of deionized water were added to a high-pressure reactor, stirred to dissolve, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C., and the pressure in the reactor was controlled not to be higher than 0.3 MPa. 41.8 kg of propylene oxide (molecular weight 58, 720 mol, the molar ratio of propylene oxide to ethanolamine was 1.8:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40° C. Then, 78.31 kg of the reaction product (alcoholamine hydrate AA1a, or alcoholamine composition AA1a) was discharged from the reactor, and the viscosity (25° C.) was 291 centipoise. The product was sampled and the content of ethanol isopropanolamine in the amine hydrate AA1a was measured by gas chromatography. The content of ethanol diisopropanolamine was 80.1 mol, the content of ethanol diisopropanolamine was 319.8 mol, and the molar ratio of ethanol diisopropanolamine to ethanol isopropanolamine was 4:1. 1 H-NMR spectrum is shown in Figure 5 The water content of the alcoholamine hydrate AA1a was determined by Karl Fischer method to be 15.6 wt %.

[0079] Then, 40 kg of the above obtained alcoholamine hydrate AA1a was added to an autoclave, and carbon dioxide gas was introduced into the alcoholamine hydrate AA1a under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder was controlled to be no higher than 0.3 MPa, and the temperature was controlled between 40-50°C, and the temperature was controlled to react for 3 hours. After the temperature was lowered to below 40°C, the pressure was released and the product was discharged to obtain a carbonate alcoholamine salt composition AA1b (or alcoholamine composition AA1b), wherein the CO2 absorption amount was 792 g (about 18 mol, i.e., 17.5 mol% of the alcoholamine in AA1a was neutralized by CO2 to form carbonate alcoholamine salt; CO2 content was 1.94 wt%). The dynamic viscosity (25°C) of the product AA1b was 489 centipoise. The pH of the product AA1b measured by a pH meter (Ray Magnet PHS-3C, Shanghai Yidian Science Instrument Co., Ltd.) was 10.8. Its decomposition temperature is between 45℃ and 68℃.

[0080] Preparation Example 2 (preferred)

[0081] 24.42 kg of ethanolamine (molecular weight 61, 400.3 mol) and 14.5 kg of deionized water were added to an autoclave, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C., and the pressure in the reactor was controlled to be no higher than 0.3 MPa. 35.00 kg of propylene oxide (molecular weight 58, 603 mol, the molar ratio of propylene oxide to ethanolamine was 1.5:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40° C. Then, 73.7 kg of the reaction product (alkanolamine hydrate AA2a, or alkanolamine composition AA2a) was discharged from the reactor. The product was sampled and the content of ethanol isopropanolamine in the alkanolamine hydrate AA2a was measured by gas chromatography to be 200.1 mol, the content of ethanol diisopropanolamine was 199.7 mol, and the molar ratio of ethanol diisopropanolamine to ethanol isopropanolamine was 1:1. The water content in the alcoholamine hydrate AA2a was 19.6 wt %.

[0082] Then, 40kg of the above obtained alcoholamine hydrate AA2a is added to the autoclave, and the CO output from the CO storage cylinder is controlled under the condition that the pressure of the gas is not higher than 0.3MPa, and carbon dioxide gas is introduced into the alcoholamine hydrate AA2a, and the temperature is controlled between 40-50°C, and the temperature control reaction is performed for 3 hours. After the temperature is lowered to below 40°C, the pressure is released and the product is discharged to obtain a carbonate alcoholamine salt composition AA2b, wherein the CO absorption capacity is 1.54kg (about 35mol, CO content is 3.71wt%, and about 32.2mol% of the alcoholamine in AA2a is neutralized by CO to form carbonate alcoholamine salt). The viscosity (25°C) of the product AA2b is 646 centipoises. pH=10.4, and the decomposition temperature is between 45°C and 68°C.

[0083] Preparation Example 3

[0084] 30kg of ethanolamine (molecular weight 61,491.8mol), 14kg of deionized water were added to the autoclave, stirred and dissolved, the reactor was sealed, and then under constant stirring, the temperature was controlled between 60-95°C, the pressure in the reactor was controlled to be not higher than 0.3MPa, 34.22kg of propylene oxide (590mol, the mol ratio of propylene oxide to ethanolamine was 1.2:1) was added to the reactor in batches, and the temperature control reaction was 3 hours after adding the material, and then the temperature was cooled to 40°C. Then, 78.03kg of the reaction product (alkanolamine hydrate AA3a) was discharged from the reactor, and the content of ethanol isopropanolamine in the alcoholamine hydrate AA3a was 393.0mol and 98.3mol of ethanol diisopropanolamine by gas chromatography from the product, and the mol ratio of ethanol diisopropanolamine to ethanol isopropanolamine was 0.25:1. The water content in the alcoholamine hydrate AA3a was 17.9wt%.

[0085] Then, 40 kg of the above obtained alcoholamine hydrate AA3a is added to an autoclave, and carbon dioxide gas is introduced into the alcoholamine hydrate AA3a under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder is not higher than 0.3 MPa, and the temperature is controlled between 40-50° C., and the temperature is controlled to react for 3 hours. After the temperature is lowered to below 40° C., the pressure is released and the product is discharged to obtain a carbonate alcoholamine salt composition AA3b, wherein the CO2 absorption capacity is 1.81 kg (about 41.1 mol, CO2 content is 4.33 wt%, and 32.6 mol% of the alcoholamine in AA3a is neutralized by CO2). The viscosity (25° C.) of the product AA3b is 699 centipoises. pH=11.3.

[0086] Comparative Preparation Example 1 (Comparative)

[0087] A carbonate amine salt composition product with a higher CO2 content was obtained as a comparison.

[0088] 30 kg of the alcoholamine hydrate AA3a obtained by the method of the above preparation example 3 was added to the autoclave, and carbon dioxide gas was introduced into the alcoholamine hydrate AA3a under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder was controlled to be 0.3 MPa, and the temperature was controlled between 40-50° C. The temperature was controlled to react for 3 hours, and the pressure was released after the temperature was lowered to below 40° C., and the product was discharged to obtain an alcoholamine carbonate compound AA3c (or alcoholamine composition), wherein the CO2 absorption amount was 2.905 kg (about 66 mol, CO2 content was 8.83 wt%, and about 69.8 mol% of the alcoholamine was neutralized by CO2). The viscosity (25° C.) of the product AA3c was 1706 centipoise. pH=10.3.

[0089] Preparation Example 4

[0090] This Preparation Example 4 is the same as Preparation Example 3 in the unpublished Chinese patent application CN202211123787.1 or Preparation Example 8 in the unpublished Chinese patent application CN202211123171.4.

[0091] 17.64 kg of 1,4-diamine (molecular weight 88.15, 200 mol) and 9.2 kg of deionized water were added to a high-pressure reactor, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95°C and the pressure was controlled not to be higher than 0.3 MPa. 23.232 kg of propylene oxide (molecular weight 58.079, 400 mol) was added to the reactor in batches. After the addition, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40°C. Then, about 50 kg of the reaction product (alcoholamine hydrate AA3a) was discharged from the reactor, and the pH value of the product measured by a pH meter was 13.46. Samples were taken from the product and the content of N,N,N'-tri(hydroxyisopropyl)-diamine in the alcoholamine hydrate AA3a was measured by gas chromatography to be about 0.02 mol, and the content of N,N'-di(hydroxyisopropyl)-diamine was about 199.98 mol. Its viscosity (25°C) is 324 centipoise. The water content of the alcoholamine hydrate AA3a measured by Karl Fischer method is 18.4 wt%. A sample is taken from the obtained product for testing NMR spectrum. 1 H-NMR shows Figure 4 . Figure 4 It is shown that the product of Preparation Example 4 is N,N'-di(hydroxyisopropyl)-butylene diamine. This shows that the alcohol amine product obtained by the reaction of organic amine and epoxide depends on the molar ratio of organic amine to epoxide. This alcohol amine product can also be used as a component of PU foaming agent.

[0092] Application Examples

[0093] Example 1

[0094] 1. Raw materials of white material component: weigh 65kg polyether polyol 8310 (sucrose initiator, hydroxyl value 310mg KOH / g, BEFAR GROUP CO., LTD.), 20kg of aromatic polyester polyol XCPA220-1 (hydroxyl value 220mgKOH / g, Asahikawa Chemical (Suzhou) Co., Ltd.), 10kg of polyether polyol 8038 (sorbitol initiator, hydroxyl value 380mgKOH / g, Jiahua Chemical Co., Ltd.), 5kg of toluene diamine-started polyether polyol YD401P (hydroxyl value 400mgKOH / g, Hebei Yadong Chemical Group Co., Ltd.), 1kg of catalyst TMR-2 (Air Chemicals, USA), 0.1kg of catalyst Dabco2040 (Evonik Chemical), 2kg of foam stabilizer DC3201 (Gas and Chemicals Company), 15kg of flame retardant TCPP (Jiangsu Yak Chemical Co., Ltd.), 10kg of the carbonate amine salt composition AA1b in Preparation Example 1 (wherein the molar ratio of triolamine A2 (ethanol diisopropanolamine) to diolamine A1 (ethanol isopropanolamine) is 4:1, and the CO2 content is 1.94wt%).

[0095] 2. Add the weighed polyether polyol 8310, aromatic polyester polyol XCPA220-1, polyether polyol 8038, toluene diamine-started polyether polyol 401P, catalysts TMR-2 and Dabco2040, foam stabilizer DC3201, flame retardant TCPP, and carbonate alcohol amine salt composition AA1b into the reactor in sequence, and stir slowly (180 rpm) for 1-2 hours at room temperature to mix them completely to obtain a uniform, transparent mixture (i.e., the white material component).

[0096] 3. The black material component is polymethyl polyphenyl polyisocyanate (PM200, Wanhua Chemical), with a dosage of 130 kg.

[0097] 4. At an ambient temperature of 5°C, the white component and the black component were sprayed onto a vertical cement board (substrate) at a temperature of 5°C by a Graco sprayer A-25. The foam was sprayed and foamed in a spraying manner with each layer of foam being 2-3cm thick and the total foam thickness being 20cm. During the spraying process, no phenomenon of wet foam falling off in the form of large-sized flakes or blocks was observed. After the foam was formed and matured, a polyurethane rigid foam material was obtained. The performance parameters of the obtained foam product are listed in Table 1. The SEM photograph of the foam material sample is shown in Figure 1 The cell size of the foam is very uniform. After curing, no peeling of the foam from the substrate was found.

[0098] Example 2

[0099] Example 1 was repeated, except that the same amount of the alcohol amine composition AA2b of Preparation Example 2 (wherein the molar ratio of triolamine A2 (ethanol diisopropanolamine) to diolamine A1 (ethanol isopropanolamine) was 1:1, and the CO2 content was 3.71 wt%) was used instead of the carbonate alcohol amine salt composition AA1b to prepare a polyurethane rigid foam material. The SEM photograph of the foam material is shown in Figure 2 The cell size is very uniform. No large-sized flakes or chunks of wet foam were observed to fall off during the spraying process, and no peeling of the foam from the substrate was observed after curing.

[0100] Example 3

[0101] Example 1 was repeated, except that the same amount of the alcoholamine composition AA3b (the molar ratio of A2 to A1 was 0.25:1, and the CO2 content was 4.33 wt%) of Preparation Example 3 was used instead of the carbonate alcoholamine salt composition AA1b to prepare a polyurethane rigid foam material. In the spraying process, no phenomenon of wet foam falling off in the form of large-sized flakes or blocks was observed, and no phenomenon of foam peeling off from the substrate was found after curing.

[0102] Comparative Example 1

[0103] The operation process is repeated in Example 1, except that the more active ethylenediamine-started polyether polyol YD403 is used instead of the toluene diamine-started polyether polyol YD401P, and the carbonate alcohol amine salt composition AA3c with a higher CO2 content of Comparative Preparation Example 1 is used instead of the carbonate alcohol amine salt composition AA1b.

[0104] 1. Raw materials of white material component: weigh 65kg polyether polyol 8310 (sucrose initiator, hydroxyl value 310mg KOH / g, BEFAR GROUP CO., LTD.), 20kg aromatic polyester polyol XCPA220-1 (hydroxyl value 220mgKOH / g, Asahikawa Chemical (Suzhou) Co., Ltd.), 10kg polyether polyol 8038 (sorbitol initiator, hydroxyl value 380mgKOH / g, Jiahua Chemical Co., Ltd.), 5kg ethylenediamine-initiated polyether polyol YD403 (ethylenediamine-initiated polyoxypropylene polyol, hydroxyl value 770±40mg KOH / g, Hebei Yadong Chemical Group Co., Ltd.), 1kg catalyst TMR-2 (Air Chemicals, USA), 0.1kg catalyst Dabco2040 (Evonik Chemical), 2kg foam stabilizer DC3201 (Gas & Chemicals Company), 15kg flame retardant TCPP (Jiangsu Yak Chemical Co., Ltd.), 10kg of carbonate amine salt composition AA3c in comparative preparation example 1 (wherein the molar ratio of triolamine A2 (ethanol diisopropanolamine) to diolamine A1 (ethanol isopropanolamine) is 0.25:1, and the CO2 content is 8.83wt%).

[0105] 2. Add the weighed polyether polyol 8310, aromatic polyester polyol XCPA220-1, polyether polyol 8038, ethylenediamine-started polyether polyol YD403, catalysts TMR-2 and Dabco2040, foam stabilizer DC3201, flame retardant TCPP, and carbonate alcohol amine salt composition AA3c into the reactor in sequence, and stir slowly (180 rpm) for 1-2 hours at room temperature to mix them completely to obtain a uniform, transparent mixture (i.e., the white material component).

[0106] 3. The black material component is polymethyl polyphenyl polyisocyanate (PM200, Wanhua Chemical), with a dosage of 130 kg.

[0107] 4. At an ambient temperature of 5°C, the white component and the black component were sprayed onto a vertical cement board (substrate) at a temperature of 5°C by a Graco sprayer A-25. Each layer of foam was 2-3cm thick and the total thickness of the foam was 20cm. During the spraying process, it was observed that the wet foam fell in the form of large blocks. After the foam was formed and matured, a polyurethane rigid foam material was obtained. The performance parameters of the obtained foam product are listed in Table 1.

[0108] The cured polyurethane foam on the cement board (substrate) was cut open with an electric saw and the cross section was observed. It was found that the cured foam was cracked from the substrate to form a crack (shown by reference numeral 1) and cracked between two adjacent foam layers to form a crack (shown by reference numeral 2). Figure 3 as shown in .

[0109] The results of Comparative Example 1 show that when a polyether polyol with higher activity (e.g., ethylenediamine-started polyether polyol) and a carbonate amine salt composition with a higher CO2 content are used, the wet foam is observed to fall off in the form of larger pieces during the spraying process, and for the cured foam, the foam is found to be peeled off from the substrate.

[0110] Table 1 - Performance parameters of foam materials

[0111]

[0112] Note: The compressive strength is measured for the foam specimen in the Z direction (perpendicular to the substrate), and "cracking" means that the cured foam cracks from the substrate or cracks between two adjacent foam layers. "Slightly uniform" means that the cell size is moderately uniform.

[0113] As can be seen from Table 1 above, when the amine composition (AC) of the present invention is used as a chemical foaming agent in combination with a specific polymer polyol composition, there is no drop of wet foam during the spraying process, and the prepared polyurethane rigid foam material has excellent overall performance, low thermal conductivity and good thermal insulation performance.

Claims

1. A polymer polyol composition for foaming, comprising (I) 100 parts by weight of a polymer polyol, the polymer polyol comprising: 1) 55-75 wt% of sucrose-based polyether polyol, having a hydroxyl value in the range of 290-420 mgKOH / g; 2) 15-25wt% of aromatic polyester polyol, whose hydroxyl value is in the range of 210-550mgKOH / g; 3) 5-15wt% of sorbitol-started polyether polyol, whose hydroxyl value is in the range of 340-520mgKOH / g; 4) 3-7wt% of toluenediamine-started polyether polyol, whose hydroxyl value is in the range of 350-580mgKOH / g; Wherein the weight percentages are based on the total amount of components 1)-4); (II) 3.5-20 parts by weight of an auxiliary agent, wherein the auxiliary agent includes a catalyst, a foam stabilizer and an optional flame retardant; (III) 6-20 parts by weight of a CO2- and water-containing alcoholamine composition (AC) as a blowing agent; the alcoholamine composition (AC) comprises or consists of or is mainly composed of the following components: (1) ethanol isopropanolamine (A1); (2) ethanol diisopropanolamine (A2); and (3) Water; Wherein, the molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.2-6):1; wherein the content of water is 5-38 wt %, based on the total weight of the alcoholamine composition (AC); The total content of (A1) + (A2) + water is 90-100 wt %, based on the total weight of the alcoholamine composition (AC); Wherein, a portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 1-7 wt% based on the total weight of the alcoholamine composition (AC).

2. The foaming polymer polyol composition according to claim 1, wherein: The polymer polyol comprises: 1) 60-70 wt% of sucrose-based polyether polyol, whose hydroxyl value is in the range of 290-420 mgKOH / g; 2) 17-23 wt% of aromatic polyester polyol, whose hydroxyl value is in the range of 210-550 mgKOH / g; 3) 7-13 wt% of sorbitol-based polyether polyol, whose hydroxyl value is in the range of 340-520 mgKOH / g; 4) 4-6 wt% of toluenediamine-based polyether polyol, whose hydroxyl value is in the range of 350-580 mgKOH / g; wherein the weight percentages are based on the total amount of components 1)-4); and / or (II) the auxiliary agent comprises 0.5-2.5 parts by weight of a catalyst, 1-4 parts by weight of a foam stabilizer and 0-18 parts by weight of a flame retardant, the sum of the weights of the three being 3.5-20 parts by weight, based on 100 parts by weight of the polymer polyol; and / or In the alcoholamine composition (AC), the water content is 7-35 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 1.2-6.5 wt%; and / or At an ambient temperature of 25°C, the CO2- and water-containing alcoholamine composition (AC) is in the form of a homogeneous liquid having a viscosity of 200-1000 centipoise; and / or The aromatic polyester polyol is polyethylene phthalate glycol, polyethylene diethylene phthalate glycol and / or polyethylene / diethylene phthalate glycol; and / or The total content of (A1)+(A2)+water is 92-100 wt %, based on the total weight of the alkanolamine composition (AC).

3. The foaming polymer polyol composition according to claim 1 or 2, wherein: 1) sucrose-based polyether polyols having a hydroxyl value in the range of 300-400 mgKOH / g; 2) aromatic polyester polyols having a hydroxyl value in the range of 220-500 mgKOH / g; 3) sorbitol-based polyether polyols having a hydroxyl value in the range of 350-490 mgKOH / g; 4) toluenediamine-based polyether polyols having a hydroxyl value in the range of 360-550 mgKOH / g; and / or (II) the auxiliary agent comprises 1-2 parts by weight of a catalyst, 1.5-3 parts by weight of a foam stabilizer and 0-15 parts by weight of a flame retardant, the sum of the weights of the three being 3.5-20 parts by weight; and / or In the alcoholamine composition (AC), the water content is 8-33 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 1.5-6.0 wt%; and / or At an ambient temperature of 25°C, the CO2- and water-containing alcoholamine composition (AC) is in the form of a homogeneous liquid having a pressure of 250-900 centipoise; and / or A CO2- and water-containing alcohol amine composition (AC) as a blowing agent is used in an amount of 7 to 18 parts by weight, based on 100 parts by weight of the polymer polyol; and / or The molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.25-5.5):1; and / or The total content of (A1)+(A2)+water is 94-100 wt %, based on the total weight of the alkanolamine composition (AC).

4. The foaming polymer polyol composition according to claim 3, wherein: In the alcoholamine composition (AC), the water content is 10-30 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 1.8-5.7 wt%; and / or A CO2- and water-containing alcohol amine composition (AC) as a blowing agent is used in an amount of 8-16 parts by weight; and / or The molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.3-5):1; and / or The total content of (A1)+(A2)+water is 95-100 wt %, based on the total weight of the alcoholamine composition (AC).

5. The foaming polymer polyol composition according to claim 4, wherein: In the alcoholamine composition (AC), the water content is 12-28 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 2.0-5.5 wt%; and / or A CO2- and water-containing alcohol amine composition (AC) as a blowing agent is used in an amount of 9-14 parts by weight; and / or The molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.4-4.5):1; and / or The total content of (A1)+(A2)+water is 96-100 wt %, based on the total weight of the alcoholamine composition (AC).

6. The foaming polymer polyol composition according to claim 5, wherein: In the alcoholamine composition (AC), the water content is 15-25 wt%; and / or A portion of the alcoholamine in the alcoholamine composition (AC) is neutralized by CO2 so that the content of CO2 in the alcoholamine composition (AC) is 2.5-5.0 wt%; and / or The molar ratio of ethanol diisopropanolamine (A2) to ethanol isopropanolamine (A1) is (0.5-4):1; and / or The total content of (A1)+(A2)+water is 97-100 wt %, based on the total weight of the alcoholamine composition (AC).

7. The foaming polymer polyol composition according to claim 1 or 2, wherein: The alcoholamine composition (AC) is prepared by the following preparation method: 1) allowing ethanolamine and propylene oxide to react in the presence of water to obtain an alcoholamine composition (AC) containing ethanol diisopropanolamine (A2) and ethanol isopropanolamine (A1); wherein the molar ratio of propylene oxide to ethanolamine is (1.2-1.9):1; The amount of water used in step 1) is such that the water content in the resulting olamine composition (AC) is as defined above; for example, such that the water content in the olamine composition (AC) is 5-38 wt %, based on the total weight of the olamine composition (AC). 2) introducing CO2 gas into the obtained alcoholamine composition (AC) to partially neutralize the alcoholamine compound in the composition (AC), thereby obtaining an alcoholamine composition (AC) containing CO2 and water; The amount of CO2 introduced is such that the content of CO2 in the alcoholamine composition (AC) is 1-7 wt %, based on the total weight of the alcoholamine composition (AC).

8. The foaming polymer polyol composition according to claim 7, wherein: The molar ratio of propylene oxide to ethanolamine is (1.3-1.85):1; and / or The amount of CO2 introduced should be such that the content of CO2 in the alcoholamine composition (AC) is 1.2-6.5 wt%, based on the total weight of the alcoholamine composition (AC); and / or The water content in the alkanolamine composition (AC) is 7-35 wt%.

9. The foaming polymer polyol composition according to claim 8, wherein: The molar ratio of propylene oxide to ethanolamine is (1.4-1.83):1; and / or The amount of CO2 introduced should be such that the content of CO2 in the alcohol amine composition (AC) is 1.5-6.0 wt %, based on the total weight of the alcohol amine composition (AC); and / or The water content in the alkanolamine composition (AC) is 8-33 wt%.

10. The foaming polymer polyol composition according to claim 9, wherein: The molar ratio of propylene oxide to ethanolamine is (1.5-1.8):1; and / or The amount of CO2 introduced should be such that the content of CO2 in the alcohol amine composition (AC) is 1.8-5.7 wt%, based on the total weight of the alcohol amine composition (AC); and / or The water content in the alkanolamine composition (AC) is 10-30 wt%.

Citation Information

Patent Citations

  • Process for separating components from ethanolamine mixtures

    CA1003358A

  • Novel preparation method for mono ethanol diisopropanolamine

    CN103435499A

  • Monoethanol diisopropanol amine production method

    CN107663157A

  • Carbonated alcohol amine salts derived from c4-C6 alkanediamine and blowing agent compositions

    CN117430517A

  • Alcohol amine compositions and their use as polyurethane blowing agents

    CN117447755A